Remifentanil for Carboprost-Induced Adverse Reactions During Cesarean Delivery Under Combined Spinal-Epidural Anesthesia - Wei, Chang-na; Chang, Xiang-yang; Dong, Jin-hua; Zhou, Qing-he (Frontiers in Pharmacology, 2020)
Abstract Purpose: Carboprost may induce adverse reactions when used to treat postpartum hemorrhage. We aimed to explore the effects of intravenous infusion of low-dose remifentanil to prevent such reactions. Methods:We enrolled parturient patients scheduled for elective cesarean section. Anesthesiologist administered combined spinal epidurals at the L3/4 interspace, with 0.5% hyperbaric bupivacaine subarachnoid space injections (1.5–2.5 mL). We randomly divided parturient patients, administered carboprost during surgery, into the remifentanil group (group R) and the control group (group C). Patients in group R received an intravenous target-controlled infusion of remifentanil (target effect-site concentration, 1.5 ng/mL) simultaneously with a carboprost tromethamine injection (250 µg). Patients in group C received a normal saline infusion with carboprost. We recorded and analyzed the incidence of carboprost-related adverse reactions (vomiting, nausea, chest congestion, flushing, hypertension, tachycardia, cough, and shivering), and assessed patient comfort using a numerical rating scale ([NRS], on which 0 was very uncomfortable and 10 was very comfortable). Results:After applying inclusion and exclusion criteria, we conducted statistical analysis of the data from 70 women. The incidence of vomiting was significantly lower in group R than in group C (14.3% vs. 51.4%, p < 0.01); and the incidence of nausea, chest congestion, facial flushing, and hypertension were significantly lower in group R than in group C (all p < 0.01). Furthermore, the patients’ comfort scores were significantly higher in group R than in group C (8.0 ± 1.8 vs. 3.6 ± 2.1, p < 0.01). Conclusion: Our results demonstrate that an intravenous low-dose remifentanil infusion can effectively prevent carboprost-related adverse reactions during cesarean delivery under combined spinal and epidural anesthesia. Reporting clinical trials: We pre-registered this study at http://www.chictr.org.cn/showproj.aspx?proj=27707 (ChiCTR1800016292)